Critical roles for CCR2 and the therapeutic potential of cenicriviroc in periodontitis: A pre‐clinical study. (4th August 2022) - Jiang, Wenting; Xu, Tao; Yuan, Shasha; Wei, Yiping; Song, Zhanming; Li, Qingqing; She, Shaoping; Wang, Xuekang; Wang, Cui; Yang, Gang; Cao, Jie; Sun, Fei; et al.
Abstract: Aim: CCR2 plays important roles in many inflammatory and bone metabolic diseases, but its specific role in periodontitis is unknown. In the present study, we aimed to explore the role of CCR2 in the progression of periodontitis and evaluate the effect of cenicriviroc (CVC) on periodontitis. Materials and Methods: The expression of CCR2 was studied in patients with periodontitis and in ligation‐induced murine model of periodontitis. The role of CCR2 in promoting inflammation and bone resorption in periodontitis was evaluated in Ccr2 −/− mice and wild‐type mice. The effect of CVC in the prevention and treatment of periodontitis was evaluated by systemic and local medication. Microcomputed tomography, haematoxylin and eosin staining, tartrate‐resistant acid phosphatase staining, quantitative real‐time polymerase chain reaction, enzyme‐linked immunosorbent assay, and flow cytometry were used for histomorphology, molecular biology, and cytology analysis, respectively. Results: In this study, we demonstrated that CCR2 was highly expressed in human and murine periodontitis and that CCR2 deficiency was associated with decreased inflammatory monocyte and macrophage infiltration and inflammatory mediators, osteoclast number and alveolar bone resorption. Prevention and treatment with CVC significantly reduced the severity of periodontitis, regardless of whether it was administered systemically or locally. Conclusions: CCR2 plays an important role in the development and progression of periodontitis, and CVC is a potential drug for the prevention and treatment of periodontitis.